A Study of Effective Dual Language Program Models for Non-Native Spanish Speakers - Roberts, Krystal (JETL (Journal of Education, Teaching and Learning), 2024)
As the United States population becomes increasingly ethnically and linguistically diverse, more school districts, families, and students are beginning to recognize the need and value of bilingual education, specifically dual language programs, for both native and non-native Spanish speakers (Collier & Thomas, 2020). With dual language programs on the rise, it is important to consider which program model(s) most benefit the students within a particular program. The purpose of this explanatory sequential mixed methods study was to compare the effect of different dual language program models (including immersion programs) on primary-level students’ Spanish and English language acquisition by the time students reach fourth grade. The study fRobocused specifically on non-native Spanish speakers, utilizing both quantitative and qualitative data. Such data included Spanish and English literacy levels of students who had been in a dual language program from kindergarten through fourth grade and evidence from surveys and interviews of students and teachers. The study compared two schools, one with an 80:20 program model and one with a 50:50 program model. Overall, School 1’s 80:20 dual language program model appeared to be more effective than School 2’s 50:50 model in equally developing students’ Spanish and English language acquisition. Teachers and students from both schools indicated room for growth in their respective programs.